Development and Application of Intragenic Markers for 14 Nitrogen-Use Efficiency Genes in Rice (Oryza sativa L.) - Li, Pingbo; Li, Zhen; Liu, Xu; Zhang, Hua; Wang, Qingguo; Li, Nana; Ding, Hanfeng; Yao, Fangyin (Frontiers in Plant Science, 2022)
Asian cultivated rice consists of two main subspecies, xian/indica (XI) and geng/japonica (GJ). It is well known that GJ accessions have significantly lower nitrogen-use efficiency (NUE) than XI accessions, and massive amount of nitrogen fertilizer is applied in order to achieve high grain yield. Thus, genetic improvement of NUE in GJ cultivars is in urgent need. In this study, we conducted haplotype analysis of 14 cloned NUE genes using 36 rice germplasm accessions with high-quality reference genome and developed 18 intragenic markers for elite haplotypes of these genes, which were then used to evaluate NUE genes in another 41 genetically diverse germplasm accessions from 12 countries and 71 approved GJ cultivars from northern provinces of China. Our results showed that the elite haplotypes of 12 NUE genes are mainly existed in XI accessions, but few is distributed in GJ accessions. The elite haplotypes carried by an XI accession can reach 10, while that by a GJ accession are less than 3. Surprisingly, the elite haplotype of gene DEP1 is nearly fixed in approved GJ cultivars, and elite haplotypes of gene MYB61 and NGR5 have been introduced into some approved GJ cultivars. The developed intragenic markers for NUE genes and evaluated 77 genetically diverse rice accessions could be of great use in improvement of NUE in GJ cultivars.